Roberto SOKOLOWSKI "Introducción a la fenomenología" Tr. de Esteban Marín Ávila Morelia, México, Serie fenomenología nº 13, Jitanjáfora, 2012 - Quepons, Ignacio (Investigaciones Fenomenológicas, 2021)
-